Place-Based Scientific Inquiry A Practical Handbook for Teaching Outside - Wong Blonder, Benjamin (Taylor & Francis, 2023)
Learn how to facilitate scientific inquiry projects by getting out of the classroom and connecting to the natural environment-in your schoolyard, or in your community! Providing a contemporary perspective on how to do scientific inquiry in ways that can make teachers' lives easier and students' experiences better, this book draws on authentic inquiry, engaging with communities, and teaching through project-based learning to help students design and carry out scientific inquiry projects that are grounded in their local places. This accessible guide will help you to develop skills around facilitation, team building, and learning outdoors in schoolyards and parks, acting as a go-to toolkit for teachers to help build confidence and skills in these areas. Written according to the Next Generation Science Standards, this book supports teachers in fostering community engagement and a justice-first classroom. The approachable resources included in this book will help teachers with all levels of experience succeed in empowering students grades 3-12 in their science learning. Additional support materials including template documents for student use and for teacher planning, as well as examples of real student work, are available online. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution (CC-BY) 4.0 license